Targeting PLKs as a therapeutic approach to well-differentiated thyroid cancer. Issue 8 (August 2019) - Lin, Shu-Fu; Lin, Jen-Der; Yeh, Chun-Nan; Huang, Yu-Tung; Chou, Ting-Chao; Wong, Richard J
Abstract : Polo-like kinases (PLKs) are pivotal regulators of cell proliferation and cell survival; therefore, PLKs may be potential targets in the treatment of malignancy. The therapeutic effects of volasertib, a PLKs inhibitor for papillary and follicular thyroid cancer (known as well-differentiated thyroid cancer (WDTC)), were evaluated in this study. Volasertib inhibited cell proliferation in two papillary and two follicular thyroid cancer cell lines in a dose-dependent manner. Volasertib treatment reduced cells in the S phase and increased cells in the G2/M phase. Volasertib activated caspase-3 activity and induced apoptosis. Drug combinations of volasertib and sorafenib showed mostly synergism in four well-differentiated thyroid carcinoma cell lines in vitro . Volasertib treatment in vivo retarded the growth of a papillary thyroid tumor model. Furthermore, the combination of volasertib with sorafenib was more effective than a single treatment of either in a follicular thyroid cancer xenograft model. Promising safety profiles appeared in animals treated with either volasertib alone or volasertib and sorafenib combination therapy. These findings support volasertib as a potential drug for the treatment of patients with WDTC.